THE IMPACT OF PERCEIVED EASE OF USE ON ISLAMIC COMMERCIAL BANKS’ M-BANKING APPLICATIONS INTERVENED BY TRUST - Ghozian Hakeem; Ririn Tri Ratnasari (Jurnal Ekonomi Syariah Teori dan Terapan, 2021)
ABSTRAKPenelitian ini bermaksud untuk mengetahui pengaruh variabel perceived ease of use terhadap behavioral intention dengan trust sebagai variabel intervening pada penggunaan aplikasi m-banking bank umum syariah. Penelitian ini menggunakan pendekatan kuantitatif dengan metode path analysis dan melibatkan 50 responden yang merupakan nasabah salah satu bank umum syariah sekaligus pengguna aplikasi m-banking bank yang bersangkutan dengan metode purposive sampling secara online, serta menggunakan metode analisis jalur dengan program AMOS untuk mengolah data. Hasil penelitian menunjukkan bahwa perceived ease of use dan trust berpengaruh signifikan terhadap behavioral intention, demikian juga perceived ease of use terhadap trust. Penelitian ini juga berimplikasi pada ilmu pemasaran Islam, yaitu mengenai niat perilaku konsumen yang akan berefek pada penggunaan aplikasi m-banking bank umum syariah saat ini dan di masa mendatang, seperti perekomendasian aplikasi tersebut ke orang lain. Maka dari itu, bank umum syariah diharapkan dapat meningkatkan kualitas fitur yang terdapat di aplikasi m-banking, mempromosikan secara gencar kemudahan dan manfaat yang akan didapat dari penggunaan aplikasi m-banking agar nasabah tertarik untuk menggunakannya, serta menyederhanakan baik tampilan dan cara penggunaan, sehingga aplikasi tersebut bisa digunakan dengan mudah oleh berbagai kalangan.Kata Kunci: Perceived ease of use, trust, behavioral intention, aplikasi m-banking. ABSTRACTThe intention of this study is to discover perceived ease of use’s impact on behavioral intention with trust as the intervening variable in the usage of Islamic commercial banks’ m-banking applications. This research uses a quantitative approach with path analysis method and involves 50 participants who are customers of one of Islamic commercial banks as well as users of m-banking application of the bank concerned with online purposive sampling method. It also uses path analysis method by using AMOS program to analyze the data. The result of this study indicates both perceived ease of use and trust significantly affect behavioral intention, and so is perceived ease of use to trust. This study also implies to Islamic marketing, which refers to consumers’ behavior that will affect the current and future usage of Islamic comercial banks’ m-banking applications, such as recommending it to other people. Therefore, Islamic commercial banks are expected to improve their applications’ features, promote its convenience and benefits vigorously to attract customers to use it, and simplify both its appearance and usage method, so it can be used by anyone easily.Keyword: Perceived ease of use, trust, behavioral intention, m-banking application. DAFTAR PUSTAKAAlrawashdeh, T. A., Elbes, M. W., Almonani, A., & ElQirem, F. T. A. (2019). User acceptance model of open source software: An integrated model of OSS characteristics and UTAUT. Journal of Ambient Intelligence and Humanized Computing, 11, 3315-3327.Botsman, R., & Rogers, R. (2010). Beyond zipcar: Collaborative consumption. Harvard Business Review, 88(10), 30.Chinomona, R. (2013). The influence of perceived ease of use and perceived usefulness on trust and intention to use mobile social software. African Journal for Physical, Health Information, Recreation and Dance, 19(2). 258-273.CNN Indonesia. (2021). 180 juta umat muslim baru 30 juta jadi nasabah bank syariah. Diakses dari https://www.cnnindonesia.com/ekonomi/20210210164446-78-604821/180-juta-umat-muslim-baru-30-juta-jadi-nasabah-bank-syariah.CNN Indonesia. (2021). Penjual 91 juta data Tokopedia beraksi lagi sasar kreditplus. Diakses dari  https://www.cnnindonesia.com/teknologi/20200804102505-185-531879/penjual-91-juta-data-tokopedia-beraksi-lagi-sasar-kreditplusDavis, F. D. (1989). Perceived usefulness, perceived ease of use and user acceptance of information technology. MIS Quarterly, 13(3). 319-340. https://doi.org/10.2307/249008Dewan Perwakilan Rakyat Republik Indonesia. (1945). https://www.dpr.go.id/jdih/uu1945. 25 Januari 2021.Fishbein, M., & Ajzen, I. (1975). Believe, attitude, intention and behavior: An introduction to theory and research. Massachusets: Addison-Westlyn.Global Religious Futures. (2020). Diakses dari http://www.globalreligiousfutures.org/religions/muslimsHassan, H. E., & Wood, V. R. (2020). Does country culture influence consumers’ perceptions toward mobile banking? A comparison between Egypt and the United States. Telematics and Informatics, 46(101312), 1-14. https://doi.org/10.1016/j.tele.2019.101312Infobanknews.com. (2021). Transaksi digital banking mandiri Syariah meningkat dimasa pandemic. Diakses https://infobanknews.com/topnews/transaksi-digital-banking-mandiri-syariah-meningkat-dimasa-pandemiJaiyeoba, O. O., & Iloanya, J. (2019). E-learning in tertiary institutions in botswana: apathy to adoption. The International Journal of Information and Learning Technology, 36(2), 157-168.Jogiyanto. (2007). Sistem informasi keperilakuan. Yogyakarta: Andi.Kang, J. –W., & Namkung, Y. (2019). The role of personalization on continuance intention in food service mobile apps: a privacy calculus perspective. International Journal of Contemporary Hospitality Management. 31(2). 734-752. https://doi.org/10.1108/IJCHM-12-2017-0783Kasiram, M. (2008). Metode penelitian kuantitatif-kualitatif. Malang: UIN Malang Press.Kaur, S., & Arora, S. (2020). Role of perceived risk in online banking and its impact on behavioral intention: Trust as a moderator. Journal of Asia Business Studies, 15(1), 1-30. https://doi.org/10.1108/JABS-08-2019-0252.Kementerian Agama Republik Indonesia. (2020). Al-Qur’an surat al-anfal. Diakses dari https://quran.kemenag.go.id/sura/8Kementerian Agama Republik Indonesia. (2020). Al-Qur’an surat al-anfal. Diakses dari https://quran.kemenag.go.id/sura/108Li, Q. (2020). Healthcare at your fingertips: The acceptance and adoption of mobile medical treatment services among chinese users. International Journal of Environmental Research and Public Health, 17(6895). 1-21. DOI: 10.3390/ijerph17186895Meeprom, S., & Silanoi, T. (2020). Investigating the perceived quality of a special event and its influence on perceived value and behavioural intentions in a special event in Thailand. International Journal of Event and Festival Management, 11(3), 337-355. https://doi.org/10.1108/IJEFM-09-2019-0043Mostafa, R. B. (2020). Mobile banking service quality: a new avenue for customer value co-creation. International Journal of Bank Marketing, 38(5), 1107-1132. https://doi.org/10.1108/IJBM-11-2019-0421Namahoot, K. S., & Laohavichien, T. (2018). Assessing the intentions to use internet banking: the role of perceived risk and trust as mediating factors. International Journal of Bank Marketing, 36(2), 256-276. https://doi.org/10.1108/IJBM-11-2016-0159Oentario, Y., Harianto, A., & Irawati, J. (2017). Pengaruh usefulness, ease of use, risk terhadap intention to buy onlinepatisserie melalui consumer attitude berbasis media sosial di Surabaya. Jurnal Manajemen Pemasaran, 11(1), 26-31. https://doi.org/10.9744/pemasaran.11.1.26-31Polykalas, S. E., & Prezerakos, G. N. (2019). When the mobile app is free, the product is your personal data. Digital Policy, Regulation and Governance, 21(2), 89-101. https://doi.org/10.1108/DPRG-11-2018-0068Ratnasari, R. T., Gunawan, S., Mawardi, I., & Kirana, K. C. (2020b). Emotional experience on behavioral intention for halal tourism. Journal of Islamic Marketing, 12(4), 864-881. https://doi.org/10.1108/JIMA-12-2019-0256.Ratnasari, R. T., Gunawan, S., Septiarini, D. F., Rusmita, S. A., & Kirana, K. C. (2020a). Customer satisfaction between perceptions of environment destination brand and behavioural intention. International Journal of Creativity and Change, 10(12). 472-487.Republika. (2021). Luncurkan msyariah mega Syariah targetkan 1 juta transaksi. Diakses dari  https://www.republika.co.id/berita/qrg9e3370/luncurkan-msyariah-mega-syariah-targetkan-1-juta-transaksiRizan, M., Haro, A., & Rahmadina, B. (2019). Pengaruh perceived ease of use dan service quality terhadap customer satisfaction dengan trust sebagai intervening (Studi kasus pada pengguna Grab di wilayah Jakarta). Jurnal Riset Manajemen Sains Indonesia (JRMSI), 10(2), 337-355.Sahoo, D., & Pillai, S. S. (2017). Role of mobile banking servicescape on customer attitude and engagement. International Journal of Bank Marketing, 35(7), 1115-1132. https://doi.org/10.1108/IJBM-09-2015-0144Saleem, H., Li, Y., Ali, Z., Ayyoub, M., Wang, Y., & Mehreen, A. (2020). Big data use an its outcomes in supply chain context: the roles of information sharing and technological innovation. Journal of Enterprise Information Management, 34(4), 1121-1143, https://doi.org/10.1108/JEIM-03-2020-0119Sedianingsih, Ratnasari, R. T., Prasetyo, A., & Hendarjanto. (2019). Antecedents of recommendation and repurchase intention on medical tourism. Revista de Ciencias Humanas y Sociales, 35(23), 1277-1300.Shao, Z., Zhang, L., Li, X., & Guo, Y. (2019). Antecedents of trust and continuance intention in mobile payment platforms: the moderating effect of gender. Electronic Commerce Research and Applications, 33(January–February 2019). https://doi.org/10.1016/j.elerap.2018.100823Sharianews.com. (2021). Pengguna BCA Syariah mobile meningkat 50 persen. Diakses dari  https://sharianews.com/posts/pengguna-bca-syariah-mobile-meningkat-50-persenSokol, M. (1994). Adaptation to difficult designs: facilitating use of new technologies. Journal of Business dan Psychology, 8(3), 277-296.Thusi, P., & Maduku D. K. (2020). South African millenials’ acceptance and use of retail mobile banking apps: an integrated perspective. Computers in Human Behavior, 111(October 2020), 1-10. https://doi.org/10.1016/j.chb.2020.106405Wu, J., Zeng, M., & Xie, K. L. (2017). Chinese travelers’ behavioral intentions toward room-sharing platforms: the influence of motivations, perceived trust and past experience. International Journal of Contemporary Hospitality Management, 29(10). 2688-2707. https://doi.org/10.1108/IJCHM-08-2016-0481